A proposal of methodology for automatic indexation using noun phrases - Souza, Renato Rocha (2006)
It can be noticed that the indexing and representation strategies nowadays seems to be near the exhaustion, and it is worth to investigate new approaches to the indexing and information retrieving systems. Among these, a branch tries to consider the intrinsic semantics of the textual documents using noun phrases as descriptors instead of single keywords. We present in this article a methodology that was developed in the scope of a doctorate research.